LncRNA LINC00525 suppresses p21 expression via mRNA decay and triplex‐mediated changes in chromatin structure in lung adenocarcinoma. Issue 7 (9th June 2021) - Fang, Panqi; Chen, Hao; Ma, Zhifei; Han, Chencheng; Yin, Wenda; Wang, Siwei; Zhu, Hongyu; Xia, Wenjia; Wang, Jie; Xu, Lin; Liu, Tongyan; Yin, Rong
Abstract: Background: Emerging evidence suggests that long noncoding RNAs (lncRNAs) play crucial roles in various cancers. In the present study, we aim to investigate the function and molecular mechanism of an up‐regulated and survival‐associated lncRNA, LINC00525, in lung adenocarcinoma (LUAD). Methods: The expression level of LINC00525 in tissues was determined by quantitative reverse transcription polymerase chain reaction (RT‐qPCR) and in situ hybridization (ISH). The functional role of LINC00525 in LUAD was investigated using gain‐and loss‐of‐function approaches, both in vivo and in vitro . RNA pull‐down, RNA immunoprecipitation (RIP), chromatin immunoprecipitation (ChIP), triplex‐capture assay, dual‐luciferase assay, gene expression microarray, and bioinformatics analysis were used to investigate the potential underlying mechanisms involved. Results: LINC00525 is highly expressed in LUAD cells and tissues. Survival analysis indicated that upregulation of LINC00525 was associated with poor prognosis in patients with LUAD patients. Knockdown of LINC00525 inhibited cell proliferation and cell cycle progression in vitro . In xenograft models, LINC00525 knockdown suppressed tumor growth and tumorigenesis of tumor‐bearing mice. Mechanistically, LINC00525 epigenetically suppressed p21 transcription by guiding Enhancer Of Zeste 2 Polycomb Repressive Complex 2 Subunit (EZH2) to the p21 promoter through an formation of RNA‐DNA triplex with the p21 promoter, leading to increased trimethylation of lysine 27 on histone 3 (H3K27me3) of the p21 promoter. In addition, LINC00525 repressed p21 expression post‐transcriptionally by enhancing p21 mRNA decay. LINC00525 promoted p21 mRNA decay by competitively binding to RNA Binding Motif Single Stranded Interacting Protein 2 (RBMS2). Conclusion: Our findings demonstrate that LINC00525 promotes the progression of LUAD by reducing the transcription and stability of p21 mRNA in concert with EZH2 and RBMS2, thus suggesting that LINC00525 may be a potential therapeutic target for clinical intervention in LUAD. Abstract : We reported the dual function of LINC00525 in fine‐tuning p21 production at both the transcriptional and post‐transcriptional levels. We suggest that LINC00525 may represent a potential therapeutic target for clinical intervention in lung adenocarcinoma.